SMAP soil moisture drying more rapid than observed in situ following rainfall events - Peter J. Shellito; Eric E. Small; Andreas Colliander; Rajat Bindlish; Michael H. Cosh; Aaron A. Berg; David D. Bosch; Todd G. Caldwell; David C. Goodrich; Heather McNairn; John H. Prueger; Patrick J. Starks; et al. (Geophysical Research Letters)
Abstract We examine soil drying rates by comparing surface soil moisture observations from the NASA Soil Moisture Active Passive (SMAP) mission to those from networks of in situ probes upscaled to SMAP's sensing footprint. SMAP and upscaled in situ probes record different soil drying dynamics after rainfall. We modeled this process by fitting an exponential curve to 63 drydown events: the median SMAP drying timescale is 44% shorter and the magnitude of drying is 35% greater than in situ measurements. We also calculated drying rates between consecutive observations from 193 events. For 6 days after rainfall, soil moisture from SMAP dries at twice the rate of in situ measurements. Restricting in situ observations to times of SMAP observations does not change the drying timescale, magnitude, or rate. Therefore, observed differences are likely due to differences in sensing depths: SMAP measures shallower soil moisture than in situ probes, especially after rainfall.